Papel dos inflamassomas NLRP3 e NAIP/NLRC4 no controle da infecção por Trypanosoma cruzi em macrófagos - Cardoso, Felipe Daniel [UNIFESP] (2019)
Inflammasomes are high-molecular-weight multiprotein complexes that activate inflammatory caspases and are assembled in the cell cytoplasm after infection and cell damage. Among the inflammasomes, those formed by the proteins NLRP3 and NAIP/NLRC4 are the most studied. Inflammasomes assembled by NLRP3 respond to alterations in the intracellular environment caused by a diversity of sterile and non-sterile stimuli. In contrast, the NLRC4 inflammasomes are assembled mainly in response to bacterial stimuli. However, recently it has been described its role in non-bacterial infections and sterile pathologies. Previously, our group demonstrated the role of NLRP3 in the resistance to Trypanosoma cruzi infection. Since the role of NLRC4 in protozoan infections is unknown, the objective of this work was to evaluate NLRC4 participation in T. cruzi infection and its possible association with NLRP3. For this, peritoneal macrophages (PMs) and bone marrow-derived macrophages (BMDMs) from wild-type, knockout (for NLRP3, NLRC4 and NAIP1-7) and phophomimetics NLRC4S533D/S533D mice were used. Initially, we analyzed the T. cruzi Y isolate to be used in the experiments, since we verified that the number of cell culture passages renders T. cruzi susceptible to macrophage effector’s mechanisms, such as IL-1β and nitric oxide (NO) production. By utilizing the isolate P13, with controlled in vivo and in vitro passages, we found that T. cruzi is able to activate NLRP3 and NLRC4 in PMs and BMDMs, since the cells from Nlrp3-/- and Nlrc4-/- mice secreted significantly less IL-1β. Furthermore, NLRP3 and NLRC4 were important to the control of T. cruzi replication in macrophages, which was related to the NO production by those cells. The role of NLRC4 in the infection by T. cruzi seems dependent on NAIP and independent of its phosphorylation, since PMs Naip1-7-/- but not NLRC4S533D/S533D presented deficient NO production and were susceptible to infection, such as Nlrc4-/- PMs. Finally, NLRC4 and NLRP3 presented redundant roles in the infection by T. cruzi, suggesting that these proteins may be at the same complex. Altogether, our data describe for the first time the role of NLRC4 in the control of protozoan infection.